Upaya Penurunan Risiko Disfungsi Neurovascular Perifer Pada Pasien Dengan Post Rekontruksi Ankle Hari Ke I - Iza, Riana Nurul; , Enita Dewi, S.Kep, Ns., MN (2016)
Peripheral neurovascular dysfunction is a disorder of circulation, sensation or movement extremity. The importance of efforts to reduce the risk of peripheral neurovascular dysfunction is to minimize injury or discomfort to clients who experience changes in sensation. Peripheral neurovascular dysfunction can be characterized by pain or localized pain, paralysis or limited range of motion, pallor or distal part, paresthesias or changes in sensation, pulsesness or changes in pulse and CRT ≥ 3 seconds at the distal leg. It can also improve the adequacy of blood flow through blood vessels to nourish the nervous tissue function and the ability to convey the sensory and motor impulses.The author describes the efforts to reduce the risk of peripheral neurovascular dysfunction and provide nursing care to clients with risk of peripheral neurovascular dysfunction. The method used is descriptive case study approach, is to perform nursing care from assessment using means anamnesis or to communicate directly to obtain data by asking questions that focus on client problems and physical assessment itself is conducted to clarify the results of the anamnesis and evaluate the state of general physical and see if there are indications of other diseases , from the assessment conducted enforceable nursing diagnoses and arranged an intervention , subsequent implementation and evaluation of nursing. The act of nursing 3x24 hours in patients post-reconstruction ankle with the risk of dysfunction of neurovascular peripheral, nursing actions do is care circulation by elevating extremity disturbed 20 degrees or higher from the location of the heart and encourage clients to move the toes were disrupted by 2 -4 times per hour.Peripheral neurovascular dysfunction problem is not resolved, thus requiring further treatment and cooperation with other medical teams, clients and family is indispensable for the success of nursing care.